Beaded stream-like CoSe2 nanoneedle array for efficient hydrogen evolution electrocatalysis. Issue 12 (4th March 2016) - Lee, Chuan-Pei; Chen, Wei-Fu; Billo, Tadesse; Lin, Yan-Gu; Fu, Fang-Yu; Samireddi, Satyanarayana; Lee, Chih-Hao; Hwang, Jih-Shang; Chen, Kuei-Hsien; Chen, Li-Chyong
Abstract : Beaded-stream-like nanoneedles array based on earth-abundant and inexpensive CoSe2 efficiently splits water into hydrogen. Abstract : The development of earth-abundant and efficient electrocatalysts for the hydrogen evolution reaction (HER) is one of the keys to success for future green energy systems using hydrogen fuel. Nanostructuring of electrocatalysts is a promising way to enhance their electrocatalytic performance in the HER. In this study, pure pyrite-type beaded stream-like cobalt diselenide (CoSe2 ) nanoneedles are directly formed on flexible titanium foils through treating a cobalt oxide (Co3 O4 ) nanoneedle array template with selenium vapor. The beaded stream-like CoSe2 nanoneedle electrode can drive the HER at a current density of 20 mA cm −2 with a small overpotential of 125 mV. Moreover, the beaded stream-like CoSe2 nanoneedle electrode remains stable in an acidic electrolyte for 3000 cycles and continuously splits water over a period of 18 hours. The enhanced electrochemical activity is facilitated by the unique three-dimensional hierarchical structure, the highly accessible surface active sites, the improved charge transfer kinetics and the highly attractive force between water and the surface of the nanoneedles that exceeds the surface tension of water.